Analysis of frequency and structure of indications to cesarean section by M.S. ROBSON criteria - Gryshchenko, Olga; Shahin kizi, Mamedova Sevindzh (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Annotation. In 2001, M. S. Robson proposed a classification based on criteria to identify pregnant women whose birth is not possible naturally. The purpose of the study is to analyze the frequency and structure of indications for caesarean section to determine promising ways to optimize the management of labor. Materials and methods. Based on the final diagnoses, an analysis of the structure of the absolute and percentage number of women groups M.S. Robson, the caesarean section frequency in each group, and the caesarean section structure for individual groups in 2071 women giving birth in the Kharkov city perinatal center, including 726 (35,1 %), by caesarean section. Results. The most promising in terms of reducing the frequency of cesarean section are women of the 1st, 2d and 3rd groups. In most cases, caesarean section in these groups was performed due to complications of childbirth or in connection with obtaining new data on the risk of complications during childbirth. Among these women, a rather frequent indication for emergency surgery is primary weakness of labor (in the 1st and 3rd groups) or weakness of labor after unsuccessful induction of labor (2a and much less often – 4a group). It is this contingent of pregnant women and women in childbirth that requires special attention. On the one hand, it is a reserve to reduce the frequency of cesarean section, on the other hand, in some cases, the operation is performed late, which leads to severe depletion of the woman in labor during childbirth, complete suppression of the contractile function of the uterus with a lack of sensitivity to oxytocin and to severe hypoxic-ischemic complications in the fetus. Conclusions. To substantiate a decrease in the frequency of cesarean section, the most promising is the group of women with first or repeated births with full-term single-term pregnancy and head presentation of the fetus (groups 1 and 3 according to M.S. Robson), and with planned induction of labor (groups 2a and 4a), that make up more than 20 % of women after cesarean section. Planning the optimal tactics of labor management for these women on the basis of identifying risk factors and determining the contingent of women for whom a set of preventive and therapeutic measures is appropriate is to reduce the frequency of cesarean section.